2017
DOI: 10.1111/bjh.14686
|View full text |Cite
|
Sign up to set email alerts
|

A novel multi‐epitope vaccine from MMSA‐1 and DKK1 for multiple myeloma immunotherapy

Abstract: The identification of novel tumour-associated antigens is urgently needed to improve the efficacy of immunotherapy for multiple myeloma (MM). In this study, we identified a membrane protein MMSA-1 (multiple myeloma special antigen-1) that was specifically expressed in MM and exhibited significantly positive correlation with MM. We then identified HLA-A*0201-restricted MMSA-1 epitopes and tested their cytotoxic T lymphocyte (CTL) response. The MMSA-1 epitope SLSLLTIYV vaccine was shown to induce an obvious CTL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 46 publications
(57 reference statements)
0
40
0
1
Order By: Relevance
“…overlapping CTL, HTL and B cell epitopes have the capacity to activate humoral and cellular immune responses simultaneously, iii) linking an adjuvant to the vaccine ensures a long lasting immune response with enhanced immunogenicity, iv) the in vitro antigen expression complications as well as the difficulty of culturing the pathogens can also be avoided [35][36][37][38][39][40][41][42][43]. Designing of multi-epitope vaccines is an emerging area which has already gained importance, and the vaccines designed by this approach, have not only shown in vivo efficacy with protective immunity [44][45][46] but also entered phase-I clinical trials [39,40,47,48].…”
Section: Immune Simulationmentioning
confidence: 99%
“…overlapping CTL, HTL and B cell epitopes have the capacity to activate humoral and cellular immune responses simultaneously, iii) linking an adjuvant to the vaccine ensures a long lasting immune response with enhanced immunogenicity, iv) the in vitro antigen expression complications as well as the difficulty of culturing the pathogens can also be avoided [35][36][37][38][39][40][41][42][43]. Designing of multi-epitope vaccines is an emerging area which has already gained importance, and the vaccines designed by this approach, have not only shown in vivo efficacy with protective immunity [44][45][46] but also entered phase-I clinical trials [39,40,47,48].…”
Section: Immune Simulationmentioning
confidence: 99%
“…Similarly, the present study is centred on designing of a multi-epitope vaccine because these vaccines have advantages over traditional and single-epitope vaccines due to the following unique features: i) TCRs from various T cell subsets can recognize the multiple MHC Class I and Class II epitopes ; ii) CTL, HTL and B cell epitopes may overlap, thus, it has the capacity to induce humoral and cellular immune responses simultaneously; iii) linking an adjuvant to the vaccine enhances the immunogenicity and provides long lasting immune response; iv) the likelihood of pathological immune responses or adverse effects is lowered because it is less likely to contain unwanted components [29,30,70,[80][81][82][83]]. Further, it has been demonstrated that multi-epitope combined vaccine induce stronger CTL responses compared to those induced by a single-epitope vaccine by enhancing cellular immunity and releasing immune tolerance [29]. The cellular and humoral responses generated by the multi-epitope vaccines are highly speci c with increased cytokines production [84][85][86].…”
Section: Discussionmentioning
confidence: 99%
“…Several antigenic epitopes predicted using various immunoinformatics tools have potential translational implications [25,26]. These epitopes are used for the construction of a multi-epitope vaccine which can activate both humoral and adaptive immune responses [29,30]. The immunoinformatic approach is time saving as well as cost effective and has the potential to ensure a successful vaccine design [31].…”
Section: Introductionmentioning
confidence: 99%
“…Multiepitope vaccines enjoy the following advantages over single-epitope and classical vaccines: a) they are an assemblage of several epitopes obtained from distinct protein targets/antigens of an intended infection; b) the multiple T-cell receptors (TCRs) in the vaccine recipient can easily recognize vaccines with multiple HLA epitopes; c); they can be easily adjuvanted to improve their immunogenicity; d) they can activate antibody-mediated and cell-mediated immunological responses because of their overlapping helper T lymphocytes (HTL), CD8+ T-cell and B-cell epitopes; and e) unwanted protein antigens are excluded in such construct thereby reducing the chances of untoward effects and/ or immune responses likely to cause disease(s). [118][119][120][121][122][123] Thus producing a vaccine with these qualities can provide chances of combating most infections such as Streptococcus pneumoniae and HIV infections.…”
Section: Multiepitope Vaccinesmentioning
confidence: 99%